Lack of increased signal intensity in the dentate nucleus after repeated administration of a macrocyclic contrast agent in multiple sclerosis: An observational study. Issue 39 (September 2016) - Eisele, Philipp; Alonso, Angelika; Szabo, Kristina; Ebert, Anne; Ong, Melissa; Schoenberg, Stefan O.; Gass, Achim
Abstract : Abstract: Recently, several studies reported increased signal intensity (SI) in the dentate nucleus (DN) after repeated application of gadolinium-based contrast agents (GBCAs), suggesting a deposition of gadolinium in this location. Patients with relapsing–remitting multiple sclerosis (RRMS) frequently show increased permeability of the blood–brain barrier as part of the inflammatory process in the brain parenchyma, which theoretically might increase the risk of gadolinium deposition. In this retrospective study, we investigated a possible increasing SI in the DN after repeated administrations of the macrocyclic contrast agent gadoterate meglumine. Forty-one RRMS patients (33 women, mean age 38 years) with at least 6 prior gadolinium-enhanced examinations (single dose gadoterate meglumine) were identified. A total of 279 unenhanced T1-weighted examinations were analyzed. SI ratio differences did not differ between the first and last MRI examination, neither for the DN-to-pons ratio ( P = 0.594) nor for the DN-to-cerebellum ratio ( P = 0.847). There was no correlation between the mean DN-to-pons, or between the mean DN-to-cerebellum SI ratio and the number of MRI examinations ( P = 0.848 and 0.891), disease duration ( P = 0.676 and 0.985), and expanded disability status scale (EDSS) ( P = 0.639 and 0.945). We found no signal increases in the DN after a minimum of 6 injections of the macrocyclic GBCA gadoterate meglumine in RRMS patients. This warrants further investigations in regard to the true pathophysiologic basis of intracerebral gadolinium deposition.